O inimigo interno que ameaça a nação: um estudo sobre alteridade nos discursos de Jair Messias Bolsonaro - Paludo, Larissa Júlia (2020)
This dissertation presents a study of alterity based on the analysis of the speeches of Jair Messias Bolsonaro, selected between 2018 and 2019. For this purpose, the methodology used is Discourse Analysis, based on the studies by Orlandi (2015), by the peucheutian current of studies of language. The work brings the discussions referring to the field of nationalisms and identities, seeking to reference how these understandings have been transformed over the last centuries and how the question has been elaborated by the Humanities of the 21st century. After the theoretical framework, the National Security Doctrine is presented, which establishes a dichotomous vision between Nation and communism. The political perspective of the Doctrine is taken as Ideological Formation of Bolsonaro's statements. In the analysis, four discursive formations (FD) are identified on the analyzed speeches of the politician. The first FD is the notion that there is an internal enemy to be fought, which is communism; the second FD, based on the idea of an enemy, is the description of a scenario marked by chaos, moral degradation and political and economic crisis; the third FD is the idea that, because of this scenario, the Nation needs to be saved; finally, the last FD is the representation of military identity and how it is related to the figure of the nation's savior.